Wallenberg syndrome associated with a bifurcated hypoplastic right vertebral artery: First case report in Peru. - Campos-Gamarra, Rocío (2020)
Wallenberg syndrome is the most common ischemic stroke of the posterior circulation, caused by an atherothrombotic obstruction of the vertebral or the postero-inferior cerebellar artery. This occlusion leads to ischemia in the lateral portion of the bulb, which results in the representative triad of Horner’s syndrome, ataxia on the ipsilateral side of the lesion and sensory alterations. There is a greater risk of suffering from this condition with anatomical variations such as a hypoplastic and/or duplicated vertebral artery. The case of a 45-year-old woman admitted as an emergency due to hypoesthesia on the right side of the face and on the left side of the body, as well as dysphagia and vomiting is reported. MRI studies revealed an ischemic lesion in the right-side of the bulbar area; in the angio-MRI a hypoplastic right vertebral artery was evidenced whereas the angio-TC showed a hypoplastic and duplicated right vertebral artery. On the basis of the clinical and radiological examinations, the diagnosis of Wallenberg syndrome caused by bifurcated hypoplastic right vertebral artery ischemia, was confirmed.